Eficacia de los coadyuvantes en los agroquímicos para el cultivo de maíz (Zea mays L.) - Suarez Uca, Luis Sebastián (2022)
This collection of information emphasizes the efficacy of adjuvants in agrochemicals for the cultivation of corn (Zea mays L.). The adjuvants are important for several factors, among which are that they reduce the number and frequency of applications of chemical products, they allow to reduce the doses of pesticides without affecting their effectiveness of application in the crop and at the same time they improve the behavior of agrochemicals through the increase of the contact area, retention and absorption. The conclusions determine that there are certain agrochemical products, such as herbicides and insecticides, that in their formulation contain adjuvants with different functions, their proportion is limited by the inert materials of the product; adherents fix the product applied to the leaf blade, forming a protective film resistant to washing, so they are indicated to accompany products in which it is necessary to maintain a durable cover on the foliage; the organic coadjuvants allow to protect and potentiate the action of herbicide, fungicides, insecticides, acaricides, nutrients, which manage to allow greater adherence, coverage, permanence of all the substances that are applied via foliar; In corn cultivation, adjuvants are used with herbicides, increasing the penetration and absorption of herbicide molecules, controlling weeds and, in turn, allowing yields to be increased due to their optimal control, and the need to use adjuvants in corn varies according to with the formulation of the herbicide, the quality of the water for the application and the environmental conditions, especially its use with herbicides applied to the crop.